2021
DOI: 10.1111/1750-3841.15975
|View full text |Cite
|
Sign up to set email alerts
|

Technological and nutritional properties of amaranth‐fortified yellow cassava pasta

Abstract: Yellow cassava is an affordable starting material to design a healthy food, having high β‐carotene content. White and yellow cassava functional pasta were fortified with 50 g/kg (w/w) amaranth dry leaf powder and analyzed to evaluate the impact of cultivar difference, processing, and addition of amaranth leaf powder on the physicochemical, functional, pasting, antioxidant, and cooking properties of the white and yellow cassava pasta samples. Significant differences were observed among the cassava pasta samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The elevated presence of phytochemicals makes amaranth a natural antioxidant-rich food [ 12 ]. Its leaves are rich in protein (17.9 g/kg), calcium (44.2 mg/100 g), iron (13.6 mg/100 g), zinc (3.8 mg/100 g), vitamin A (3.3 mg/100 g), and vitamin C (25.4 mg/100 g) on a dry weight basis [ 10 ]. Numerous health benefits have been linked to this pseudocereal, given its proposed hypo-cholesterolemic and anti-tumorigenic effects, immunomodulatory activity, anti-allergic action, impact on hepatic and glycemic function, and activity against celiac disease as a gluten-free product [ 15 , 46 ].…”
Section: Nutritional Value Of Underutilized Grains As the Basis For T...mentioning
confidence: 99%
“…The elevated presence of phytochemicals makes amaranth a natural antioxidant-rich food [ 12 ]. Its leaves are rich in protein (17.9 g/kg), calcium (44.2 mg/100 g), iron (13.6 mg/100 g), zinc (3.8 mg/100 g), vitamin A (3.3 mg/100 g), and vitamin C (25.4 mg/100 g) on a dry weight basis [ 10 ]. Numerous health benefits have been linked to this pseudocereal, given its proposed hypo-cholesterolemic and anti-tumorigenic effects, immunomodulatory activity, anti-allergic action, impact on hepatic and glycemic function, and activity against celiac disease as a gluten-free product [ 15 , 46 ].…”
Section: Nutritional Value Of Underutilized Grains As the Basis For T...mentioning
confidence: 99%
“…Amaranth grains can be processed into various forms, such as expanded, roasted, flaked, extruded, and ground into flour, and can be used to make bakery products, biscuits, pasta, pastries, confectionery, breakfast cereals, and energizing bars [33,34,92,133]. Amaranth is the most studied pseudocereal for bread making [68].…”
Section: Other Usesmentioning
confidence: 99%
“…They are a rich source of iron (72–174 mg/kg), calcium (1300–2850 mg/kg), sodium (160–480 mg/kg), magnesium (2300–3360 mg/kg) and zinc (36.2–40 mg/kg) [ 60 ]. That is why amaranth flour can reduce the deficiency of calcium, magnesium and iron in gluten-free products and in the gluten-free diet, which can be deficient in these minerals [ 85 , 92 ].…”
Section: Buckwheat and Amaranth: Raw Materials For Brewingmentioning
confidence: 99%
“…Previous studies examined the rich nutritional profile of these leafy vegetables. Lawal et al 13 reported that Amaranthus contain 12.6 g per 100 g protein, 3.3 g per 100 g crude fibre, 6.4 mg per 100 g iron, and 1.7 mg per 100 g zinc on dry weight basis while Akwaowo et al , 14 noted that Telfairia occidentalis fresh leaves contain 22.4 g per 100 g protein, 14.2 g per 100 g crude fibre, 3.6 mg per 100 g iron, and 4.2 mg per 100 g zinc. The superior nutritional profile and the blood-glucose-lowering effect of these two vegetables have been reported by various authors 15,16 thus their hypoglycemic activities could be utilised to produce functional food product.…”
Section: Introductionmentioning
confidence: 99%
“…The unique combination between increasing consumption of cassava pasta in countries where this crop is a staple food and the interest in gluten-free alternatives in Western countries prompted us to study the techno-functional characteristics of YCP fortified with leafy vegetables powders. 13,21 Yellow cassava, having no gluten network to entrap the starch granules, has a high GI. 30,31 However, we hypothesized that the insoluble dietary fibre of the leafy vegetables can also create a network to delay starch hydrolysis while the polyphenols in the vegetables can also reduce amylase activity.…”
Section: Introductionmentioning
confidence: 99%